PEMODELAN GEOLOGI BAWAH PERMUKAAN UNTUK MENGHITUNG CADANGAN HIDROKARBON FORMASI TENSLEEP BAGIAN ATAS MENGGUNAKAN METODE VOLUMETRIK PADA LAPANGAN TEAPOT DOME,WYOMING, U.S.A - Dessy Natalia Renwarin; Leslie.S. Loppies (Department of Mechanical Engineering, 2023)
One of the evaluations of work that is widely carried out in a petroleum industry is the estimate of oil and gas reserves that can be taken in a reservoir. The estimated oil and gas reserves are part of the business activities of an oil company which includes the estimated income obtained from the production and sale of oil and gas reserves. While the reserve itself can be interpreted as the amount (volume) of oil and or gas in the reservoir that has been found It is known that the estimation and calculation of hydrocarbon reserves is very important, so this causes many oil companies to try to find the most appropriate method to obtain accurate results, thus bringing huge profits to an oil and gas company. In this paper, the study was conducted using a volumetric method to calculate hydrocarbon reserves in the upper Tensleep formation at the Teapot Dome Field. The determination of hydrocarbon fluid contact in the top Tensleep formation is assumed to have only oil-water contact (OWC) found at a depth of -5452 SSTVD where fluid in the form of oil is obtained so that the equation used in this study is the original oil in place (OOIP) equation and uses the input parameter values from petrophysical analysis in previous studies. The parameter values used include porosity values of 7.4%, water saturation values of 53.37%, net to gross values of 0.39. 4. The results of the study showed that the estimated reserves that can be calculated in the Top Tensleep formation of the Teapot Dome field have a pore volume of 232.49 MMRB. From these results, the original oil in place (OOIP) value was obtained at 121.42 STB.Keywords: Subsurface Modeling, Hydrocarbon Reserves, Tensleep Formation, OOIP, Volumetric, Teapot Dome.